Joint specific contribution of mechanical power and work during acceleration and top speed in elite sprinters - Braunstein, B.; Goldmann, J. P.; Albracht, K.; Sanno, M.; Willwacher, S.; Heinrich, K.; Herrmann, V.; Brüggemann, G. P. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of the study was to quantify and compare sprint mechanics of elite female sprinters (N=9; PB 11.4+-0.2s) during acceleration (1st, 2nd, 3rd step) and top speed (`flying 30m) running. Three dimensional kinetics and kinematics were measured on an IAAF indoor track armed with four force plates and 16 cameras. The comparison between the 1st, 2nd and 3rd step and the `flying 30m` (vave= 9.0+-0.2 ms-1) shows a progressive change in absorption and generation of mechanical power. Whilst the knee extensors where able to minimize energy absorption during acceleration, the ankle extensors showed a stretch-shortening cycle and a small absorption from the first step. This energy loss at the ankle joint does not necessarily leads to a decrease in sprint performance, it also offers the plantar flexors to work in an stretch-shortening cycle instead of concentric only mode.